FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA PT SHAFCO MULTI TRADING MEDAN - Yurmaini Yurmaini; Karmila Karmila (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
This study is shown to determine the factors that influence purchasing decisions at PT. Safco Multi Trading Medan. Price and product quality as independent variables and purchasing decisions as dependent variables. The method used in this research is to use quantitative research. Data obtained and analyzed using multiple linear regression equation with the equation Y = 4.020 + 0.378X1 + 0.500X2. This analysis includes the t test in the effect of price on purchasing decisions is 3.619 with Sig 0.001 and the t test in the effect of product quality on purchasing decisions is 5.639 with Sig 0.000, R-Square of 0.391, f test of 26.355 with Sig 0.000. The results showed that the price had a positive and significant effect on purchasing decisions at customers of PT. Shafco Multi Trading. Product quality has a positive and significant effect of 39.1% on purchasing decisions at customers of PT. Shafco Multi Trading, purchasing decision is a moderating variable in influencing product quality on purchasing decisions at PT. Shafco Multi Trading so that 60.9% is influenced by other factors not examined by researchers.